(untitled) (Baghdad Science Journal, 2019)
A groundwater quality assessment has been carried out in northeast part of Anbar governorate in western Iraq. We analyzed hydrochemical parameters such as pH, electrical conductivity, total dissolved solids presence of ions to describe groundwater quality. The study area has the only confined aquifer within the geological formation extended in area. Values of groundwater hydrochemical parameters were ranged from (7) to (7.9) for ph, (1599) to (6800) µmhos/cm for electrical conductivity (EC) and (1048) to (4446) mg/l for total dissolved solids (TDS). The origins and types of groundwater in the area were of marine origin and MgCl2 water type while only (6) samples were of continental origin and Na2SO4 water type. Groundwater utilization indicated that it can’t be used for drinking purposes, while few groundwater wells can be used for agricultural and (33) groundwater samples can be used for animal purposes. However, the nature of the soil in the area and the depth of the groundwater qualified water for agricultural uses in significant and wide ranges.